Politics of memory in the works of Rosângela Rennó: body, trauma and anachronism - Ana Lúcia Mandelli de Marsillac; Gerusa Morgana Bloss; Lucas de Oliveira Alves (Funes)
This article establishes a discussion in the scope of memory policies based on two works of Rosângela Rennó: Cicatriz and Imemorial. The works are analyzed through a hybrid understanding of memory, articulating concepts from Sigmund Freud and Walter Benjamin, as well as from authors that allow us to relaunch issues related to the body, trauma and anachronism, such as Hannah Arendt, Didi-Huberman, Grada Kilomba and Márcio Seligmann-Silva. Through the artist's works, we revisit and articulate the bodies and the history traumas, both marked by exclusion, forgetfulness and silence. We also emphasize the need for narratives capable of harboring their marks and elaborating new possibilities of existence. In this way, we seek to expand the reverberations of the inexorable marks of bodies and times.